The Diversity of Discourse Markers on College Sophomores` Writings - Purwadina, Abdul Razak Walad; Huda, Muhammad Ikmal (Universitas Muhammadiyah Semarang, 2017)
This study aims to analyze the variants, frequency, similarity, and difference of Discourse Markers (DMs) which used by Surabaya male and female sophomores of English education major in writing their descriptive texts. The author applies qualitative approach, document analysis design, to identify their DMs in their texts. The findings of the study show that Elaborative Marker appears as the most dominant marker rather than Inferential and Contrastive Markers. More than a half of total number DMs used by the students dominated by and. However, it indicates that the Surabaya College students have difficulty in varying DMs they used. Moreover, there is no indication of a major difference in terms of DMs variants between female and male students in their writings. This study benefit as one of the reflection form of English students ability in using DMs. Regarding the several DMs which identically used by the male and/or female students, further studies are still needed to seek a satisfactory answer to this phenomenon.